Relationship of Organik Pollutant with Abundance of Tubifex sp. on Sail River Pekanbaru City - Nabila Arumdani; Eko Purwanto; Budijono Budijono (Fakultas Perikanan dan Kelautan, Universitas Riau, 2022)
Tubifex sp. is an organism that is tolerant to enviromental pollution especially organic pollution, so that Tubifex sp. often to used as bioindiator of water pollution. The Sail River is one of the habitats of Tubifex sp. The River is located in the middle of Pekanbaru city and is influenced by various community activities along the river. These activities contribute organic pollutants to river bodies, where the higher the number of organic pollutants is expected to go downstream. This will affect the abundance of Tubifex sp. on the Sail River. The purpose of this study was to determine the relationship between organic pollutants and the abundance of Tubifex sp. in the Sail River which was conducted in August-September 2021 using the survey method. Sampling was carried out every two weeks at three stations. Data on organic pollutants and abundance of Tubifex sp. in the Sail River were statistically analyzed using the Pearson correlation test. The results obtained indicate that there is a relationship between organic pollutants and the abundance of Tubifex sp. in the Sail River, where the Sail River has been polluted by organic pollutants and the abundance of individual Tubifex sp. ranged from 8.453-35.280 ind/m3.